Comparison of the efficacy of hypertonic saline (3%) with salbutamol nebulization for treatment of acute bronchiolitis: a randomized clinical trail - Das, Rita; Saha Roy, Monish; Akter, Humayra; Hoq, Tanjina (International Journal of Contemporary Pediatrics, 2025)
Background: Acute bronchiolitis is a common respiratory condition in infants and nebulized solutions are often used as part of its management. This study compares the efficacy and safety of nebulized 3% hypertonic saline (HS) versus salbutamol with normal saline (NS) in treating bronchiolitis. Methods: This was a Randomized controlled trial conducted in the Department of Pediatrics of Chattogram Medical College Hospital and Chattogram Maa- O- Shishu Hospital, Chattogram, Bangladesh, during the period from February 2018 to February 2019. We included 204 children and divided them into two groups – Group A (Children who were given nebulized 3% HS (4 ml) with an oxygen flow rate of 6-8 l/min) and group B (Children who were given nebulized salbutamol in a dose of 0.15 mg/kg body weight in normal saline). Results: The mean age of patients was comparable between groups (8.54±4.41 vs. 8.25±4.46 months, p=0.644). Both groups had a male predominance (63.7% vs. 62.7%, p=0.885). Baseline clinical characteristics, including respiratory rate, heart rate, temperature and oxygen saturation, were similar across groups. At 72 hours, CSS showed significant improvement in both groups (p<0.001), with a greater reduction in the HS group (Group A) compared to the salbutamol group (Group B) (p=0.034). LOS was significantly shorter in the HS group, with 82.35% discharged within 72 hours compared to 55.9% in the salbutamol group (p=0.013). No adverse events were reported in either group. Conclusions: Nebulized 3% hypertonic saline demonstrated greater efficacy in reducing clinical severity scores and shortening hospital stays compared to salbutamol with normal saline, with no adverse events reported. This suggests that 3% HS is a safe and effective option for the management of acute bronchiolitis in infants.